2019
DOI: 10.7554/elife.42687
|View full text |Cite
|
Sign up to set email alerts
|

Brain-wide cellular resolution imaging of Cre transgenic zebrafish lines for functional circuit-mapping

Abstract: Decoding the functional connectivity of the nervous system is facilitated by transgenic methods that express a genetically encoded reporter or effector in specific neurons; however, most transgenic lines show broad spatiotemporal and cell-type expression. Increased specificity can be achieved using intersectional genetic methods which restrict reporter expression to cells that co-express multiple drivers, such as Gal4 and Cre. To facilitate intersectional targeting in zebrafish, we have generated more than 50 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 43 publications
1
45
0
Order By: Relevance
“…In this case, recombination occurred in F2 offspring when the Cre driver and the target locus were together in the female germline cells (18/18, including Crenegative offspring) but not in the male germline cells (0/19) and not in F1 zygotes. Similar unwanted germline recombination was also observed in zebrafish Cre enhancer trap driver lines with differential expression patterns in the brain (Table 2; Tabor et al, 2019). Among the 6 lines surveyed here, 2 showed only paternal germline deletion, 1 only maternal, and 2 with a strong paternal bias.…”
Section: Broader Implications-other Recombinase Systems and Organismssupporting
confidence: 79%
“…In this case, recombination occurred in F2 offspring when the Cre driver and the target locus were together in the female germline cells (18/18, including Crenegative offspring) but not in the male germline cells (0/19) and not in F1 zygotes. Similar unwanted germline recombination was also observed in zebrafish Cre enhancer trap driver lines with differential expression patterns in the brain (Table 2; Tabor et al, 2019). Among the 6 lines surveyed here, 2 showed only paternal germline deletion, 1 only maternal, and 2 with a strong paternal bias.…”
Section: Broader Implications-other Recombinase Systems and Organismssupporting
confidence: 79%
“…The updated prosomeric model of hypothalamic organization has largely been built upon data from the Allen Developing Mouse Brain Atlas 1 , containing E11.5, E13.5, and E15.5 expression patterns of many genes involved in hypothalamic development. For both the embryonic and adult zebrafish brain several online atlas projects have been initiated by our group and others (Ronneberger et al, 2012;Randlett et al, 2015;Tabor et al, 2019). However, these anatomical gene expression frameworks are largely restricted to late embryonic and early larval stages, when most of the early patterning markers cease their broad expression and may be maintained only in a subset of differentiated neurons, making the assessment of genoarchitecture more difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Together with whole brain connectome (Hildebrand et al, 2017), single‐cell transcriptomics profiling of neurons (Raj et al, 2018) and glia (Cosacak et al, 2019; Lange et al, 2020), and knowledge on the identities, morphologies, and long‐range projections of cell populations (Kunst et al, 2019), it is now possible to study the function and development of neuronal networks in an entire vertebrate brain with single cell resolution. Moreover, registration of transgenic and experimental brains on standardized atlases (Kunst et al, 2019; Randlett et al, 2015; Tabor et al, 2019) enables scientists to identify neuronal populations involved in specific behaviors (Haesemeyer, Robson, Li, Schier, & Engert, 2018; Randlett et al, 2015; Wee et al, 2019) or diseases (Thyme et al, 2019) in an unbiased manner. Beside investigations at larval stages, recent studies at juvenile zebrafish (2–5 weeks) showed that this relatively transparent (Fore, Cosacak, Verdugo, Kizil, & Yaksi, 2019) development stage allows non‐invasive imaging (Jetti, Vendrell‐Llopis, & Yaksi, 2014; Vendrell‐Llopis & Yaksi, 2015) and exhibit cognitively demanding behaviors such as learning (Palumbo, Serneels, Pelgrims, & Yaksi, 2019; Valente, Huang, Portugues, & Engert, 2012; Yashina, Tejero‐Cantero, Herz, & Baier, 2019) and social interactions (Dreosti, Lopes, Kampff, & Wilson, 2015; Hinz & de Polavieja, 2017; Larsch & Baier, 2018; Tunbak, Vazquez‐Prada, Ryan, Kampff, & Dreosti, 2020).…”
Section: Open Questions and Opportunitiesmentioning
confidence: 99%